The value of ultrasound in transradial access cerebral angiography - Sun, Zhen; Wei, Wenyue; Jia, Congcong; Zhang, Hui; Zhou, Chen; Luo, Gang; Li, Wanying; Li, Simin; Wang, Yuhong; Guo, Shuming (Frontiers in Neurology, 2025)
BackgroundTransradial access (TRA) for cerebral angiography presents challenges such as puncture failures, prolonged procedure times, and difficulties in catheter advancement due to radial artery variations. Utilizing ultrasound guidance, which has demonstrated success in coronary angiography, may improve TRA outcomes. This study aimed to assess the efficacy of ultrasound-guided TRA in cerebral angiography, focusing on success rates, procedure duration, and patient satisfaction.MethodsA prospective, non-randomized, controlled trial included 197 patients scheduled for TRA between June 2022 and January 2024. Patients undergoing cerebral angiography through TRA were divided into control and ultrasound group. The ultrasound group underwent preoperative right upper extremity artery ultrasound assessment, with ultrasound-guided puncture for challenging cases. The primary outcomes were procedure completion rate, duration, patient satisfaction, and complication rates. Statistical analyses were performed using Student’s t-test for continuous variables and the chi-square test for categorical variables to compare these outcomes between the two groups, using a two-tailed significance level of p < 0.05.ResultsThis study included a total of 197 patients: 73 in the control group and 124 in the ultrasound group. TRA was completed in 69 patients (94.5%) in the control group and 117 patients (99.2%) in the ultrasound group. The average operation time was 0.67 ± 0.19 h in the control group and 0.55 ± 0.19 h in the ultrasound group (p < 0.001). Difficult access occurred in 15 patients (21.7%) in the control group compared with 2 patients (1.7%) in the ultrasound group (p < 0.001). No significant differences were observed in either complication rates or patient satisfaction: 8 patients (11.6%) in the control group and 9 (7.7%) in the ultrasound group (p = 0.372) had complications, while 57 patients (82.6%) in the control group and 109 (93.2%) in the ultrasound group reported satisfaction (p = 0.089).ConclusionUltrasound-guided TRA in cerebral angiography effectively mitigated challenges related to puncture failures and procedure duration, offering the potential to improve outcomes and patient satisfaction in TRA procedures.